"Only Strange Flowers Have Come to Bloom": Identity Crisis in Northeast India through the Poetry of Kynpham Sing Nongkynrih - Sankhyan, Neeraj; Sigroha, Suman (SARE: Southeast Asian Review of English, 2020)
Socio-economic and political changes effected by modernization result in overlapping and muddling of various borders and boundaries, jeopardizing the very concept of a stable identity. Although traditional or essentialist identities have an innate momentum that has made them stand the test of time, conflicts between national and ethnic identities have often led to turmoil and violence, with the former trying to suppress the latter. This is particularly so in the North-eastern regions of India that suffer from an identity crisis owing to invasion by alien cultures, oppressive attitudes of the State aimed at forcefully homogenizing cultures that are essentially heterogeneous, and the adverse consequences of modernization; all of which have jeopardized indigenous cultures and identities. The literatures from these regions respond to these homogenizing tendencies with a strong voice of resistance. Kynpham Sing Nongkynrih is one such voice that blatantly disregards the mainstream poetics. Consequently, waning cultural values and imperiled ethnic identities remain chief concerns in his poetry. This paper analyses concerns related to causes and implications of identity crisis afflicting these people as reflected in Nongkynrih’s poetry, while simultaneously positing it as a counter-culture tradition structured against the majoritarian discourse aiming to salvage a unique culture from an apparent identity crisis.